Questioning practice in the EFL classroom - Wayne Rimmer (Peoples' Friendship University of Russia (RUDN University), 2019)
Questioning has been identified in the literature as a key teaching and learning activity with the quantity and quality of questions directly linked to language acquisition and a general positive learning experience. The purpose of this empirical study was to explore patterns of questions used by EFL teachers in a classroom environment. Using an observation methodology, four teachers were observed in class and a transcript made of the questions they each asked their learners. The teachers were then asked to attempt a classification of the question types in order to gain an insight into the strategy from the perspective of teacher cognition. The results confirmed that questioning is a major teaching technique that is appreciated by teachers and manipulated for a variety of pedagogical purposes. Questions most valued by teachers as instrumental in achieving quality learning were those which guided learners to the pursuit of meaningful and motivating goals with a high degree of cognitive and linguistic challenge.